2021
DOI: 10.1186/s12933-021-01252-3
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II-induced upregulation of SGLT1 and 2 contributes to human microparticle‐stimulated endothelial senescence and dysfunction: protective effect of gliflozins

Abstract: Background Sodium-glucose cotransporter 2 (SGLT2) inhibitors reduced cardiovascular risk in type 2 diabetes patients independently of glycemic control. Although angiotensin II (Ang II) and blood-derived microparticles are major mediators of cardiovascular disease, their impact on SGLT1 and 2 expression and function in endothelial cells (ECs) and isolated arteries remains unclear. Methods ECs were isolated from porcine coronary arteries, and arteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 57 publications
0
65
0
Order By: Relevance
“…Individuals carrying loss-of-function mutations in the SGLT1 gene are estimated to have a lower risk of developing heart failure, driven by mitigation of postprandial hyperglycemic episodes ( Seidelmann et al, 2018 ). In endothelial cells, angiotensin II upregulates SGLT1 expression to promote sustained oxidative stress, and inhibition of SGLT1 appears to be an attractive strategy to enhance protective endothelial function ( Park et al, 2021 ). Apart from cardiomyocytes and endothelial cells in the heart, we first identified that SGLT1 was expressed in human CFs ( Meng et al, 2018 ), and in the present study, the significant finding was that an increase in SGLT1 expression in rat hearts triggered the development of cardiac fibrosis through activation of CFs by upregulating the p38 MAPK and ERK1/2 signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals carrying loss-of-function mutations in the SGLT1 gene are estimated to have a lower risk of developing heart failure, driven by mitigation of postprandial hyperglycemic episodes ( Seidelmann et al, 2018 ). In endothelial cells, angiotensin II upregulates SGLT1 expression to promote sustained oxidative stress, and inhibition of SGLT1 appears to be an attractive strategy to enhance protective endothelial function ( Park et al, 2021 ). Apart from cardiomyocytes and endothelial cells in the heart, we first identified that SGLT1 was expressed in human CFs ( Meng et al, 2018 ), and in the present study, the significant finding was that an increase in SGLT1 expression in rat hearts triggered the development of cardiac fibrosis through activation of CFs by upregulating the p38 MAPK and ERK1/2 signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that EVs induce endothelial inflammation, haemostasis, angiogenesis, and endothelial dysfunction [ 35 ]. Thus, in addition to serving as biomarkers of vascular injury they may actually induce vascular dysfunction through direct actions on endothelial cells leading to increased oxidative stress, inflammation, and impaired endothelium-dependent vasorelaxation [ 24 , 36 – 40 ]. We and others have previously shown that endothelial EVs exert greater deleterious effects on the endothelium when formed under hyperglycaemic conditions [ 24 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Park et al extended these findings, observing that AngII was a potent inducer of SGLT1 and SGLT2 in ECs isolated from porcine coronary arteries, independently of hyperglycemia, and that these receptors had a key role to promote ultimately pro-oxidant response and endothelial deleterious effects. Interestingly, both sotagliflozin and empagliflozin prevented these effects [115].…”
Section: Gliflozin Effects On Angiotensin Systemmentioning
confidence: 99%